The Practice of Internet Marketing and Nation Brand Towards Indonesian Tourism Sectors - Suadhe Rahmat SIREGAR; Tiara WARDHANI (Indonesia Strategic Sustainability, 2023)
This thesis provides brief explanation about the important of Nation Brand and the use of Internet marketing to support Indonesian Tourism sectors. Furthermore, this paper also includes tourist perception towards Indonesia as a tourist destination. It is quite believed, as an archipelago nation with thousand cultures, natural resources, and flora and fauna, Indonesia has a capability to take a lead in tourisms sectors in Southeast Asia region. Proven by data from World Economic Forum that Indonesia position raised from 50th in 2015 into 42nd world’s rank in 2017. In Global competition, the use of internet marketing and nation brand hold significant impact to the growth of tourism industry. This terms also applied in Indonesia tourism strategic management to grow its tourism industry. The competition between Southeast Asia nations is strict, since the other nations offer more less same destination such as natural resources and cultural heritage. To strengthen and differentiate Indonesia Tourism sectors, Indonesia needs specific brands which can be used to build awareness of the people towards Indonesia. Hence, Wonderful Indonesia were created. With this paper, it will give valuable information about Indonesia Nation Brand that still need improvement. Since it is still behind three neighbor countries. There are several aspects that still need to be improved in order to gain the positive image of Nation Brands. The aspects need to be improved such as infrastructure, Natural Resources and Internet Communication and Technology.